Interlinkage between health workforce availability and socioeconomic status in rural and remote Australia. - Ellen McDonald; Ross Bailie; Peter Radchenko; K Shuvo Bakar (PLoS ONE)
Introduction Australians living in rural and remote areas experience a higher burden of disease compared to their urban counterparts, whilst having poorer access to essential health services. Socioeconomic status and health workforce shortages are important influences on health status and access to care in these areas. This research aims to provide a local-level analysis of the association between local government area (LGA) indicators of socio-economic status and health workforce availability to enhance understanding of rural and remote workforce distribution patterns. Methods Data were extracted from the Australian Bureau of Statistics and the Department of Health and Aged care, which encompassed demographic factors, socioeconomic indicators and counts for medical practitioners, allied health workers and nurses and midwives within non-metropolitan local government areas. Generalised Additive Models with Generalised Estimating Equations (GEE-GAMs) were used to test for an association between socioeconomic status (SES) and the World Health Organisation's definition of health workforce deficit. Results The odds of being in deficit of nurses and midwives increased with increasing SES. No significant association between SES and medical practitioners or allied healthcare workers was found. Very remote areas were less likely to have a deficit of allied health professionals than inner regional areas, and the same was true for nurses and midwives in both remote and very remote areas. Conclusions The findings suggest that health workforce policies that target areas of need based on SES, may have contributed to better availability of nurses and midwives in these locations, but not significantly so for medical practitioners or allied health professionals. Further research is required to investigate the relative success of workforce policies in addressing health need in relation to SES and remoteness.